Birth preference in women undergoing treatment for childbirth fear: A randomised controlled trial. Issue 6 (December 2017) - Larsson, Birgitta; Karlström, Annika; Rubertsson, Christine; Ternström, Elin; Ekdahl, Johanna; Segebladh, Birgitta; Hildingsson, Ingegerd
Abstract: Background: Childbirth fear is the most common underlying reason for requesting a caesarean section without medical reason. The aim of this randomised controlled study was to investigate birth preferences in women undergoing treatment for childbirth fear, and to investigate birth experience and satisfaction with the allocated treatment. Methods: Pregnant women classified with childbirth fear (≥60 on the Fear Of Birth Scale) (n = 258) were recruited at one university hospital and two regional hospitals over one year. The participants were randomised (1:1) to intervention (Internet-based Cognitive Behaviour Therapy (ICBT)) (n = 127) or standard care (face-to-face counselling) (n = 131). Data were collected by questionnaires in pregnancy week 20–25 (baseline), week 36 and two months after birth. Results: Caesarean section preference decreased from 34% to 12% in the ICBT group and from 24% to 20% in the counselling group. Two months after birth, the preference for caesarean increased to 20% in the ICBT group and to 29% in the counselling group, and there was no statistically significant change over time. Women in the ICBT group were less satisfied with the treatment (OR 4.5). The treatment had no impact on or worsened their childbirth fear (OR 5.5). There were no differences between the groups regarding birth experience. Conclusion: Women's birth preferences fluctuated over the course of pregnancy and after birth regardless of treatment method. Women felt their fear was reduced and were more satisfied with face-to-face counselling compared to ICBT. A higher percentage were lost to follow-up in ICBT group suggesting a need for further research.